2017
DOI: 10.1002/jhet.2935
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Mediated Synthesis of Novel 1,2,3‐Triazole‐Based Pyrazole and Pyrimidine Derivatives as Antimicrobial Agents

Abstract: In the development of novel antimicrobial agents, we synthesized novel 1,2,3‐triazole‐based pyrazole and pyrimidine derivatives 6(a–f) and 7(a–f) by ultrasound‐assisted method. The synthesized compounds were characterized by IR, 1H NMR, 13C NMR, MS, and elemental analysis. All compounds were assessed in vitro for their efficacy as antimicrobial agents against four bacteria (Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa) and two fungi (Candida albicans and Aspergillus ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…High pressure (18,000 atomic pressures) and temperature (2000–5000 K) are generated by acoustic cavitation, which influence chemical transformations [ 20 , 21 ]. The use of ultrasonication in synthesis has grown in popularity in recent years [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…High pressure (18,000 atomic pressures) and temperature (2000–5000 K) are generated by acoustic cavitation, which influence chemical transformations [ 20 , 21 ]. The use of ultrasonication in synthesis has grown in popularity in recent years [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…N ‐heterocycles have been of great research interest because of their diverse biological activities . Diazole and triazole derivatives with excellent fungicide activities have been commercialized as pharmaceuticals (miconazole) and agrochemicals (propiconazole), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The 1,2,3‐triazole‐linked pyrimidine nucleus has derived a great consideration owing to remarkable biological properties, such as antibacterial, anticancer, antivirus, and antituberculosis. Dofe et al reported the synthesis of novel 1,2,3‐triazole‐based pyrimidine as potential anti‐microbial agents . Liu et al developed the synthesis of novel 1,2,3‐triazole‐pyrimidine‐urea hybrids as potential anti‐cancer agents .…”
Section: Introductionmentioning
confidence: 99%